IMPROVING STUDENTS’ READING COMPREHENSION ON DESCRIPTIVE TEXT BY USING JIGSAW - Hermawan, Bayu; Regina, Regina; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research is aimed to improve students? reading comprehension in descriptive text by using Jigsaw technique. In conducting this research, the researcher implemented classroom action research as a method. The researcher collected the data by using observations checklist and students? assessments in each cycle. This research was conducted in two cycles. The subject of this research was 20 students at the eighth grade of SMP Mujahidin Pontianak in academic year 2017/2018. Based on the data collected, it is found that Jigsaw can improve students? activeness and participations to in teaching-learning processes from cycle to cycle. Besides, the process improvement impacted to students? mean score. The students mean score was 60.75 and in second cycle was 71.75. Since the process of learning in the second cycle showed a significant improvement, the teacher and the researcher not to conduct the next cycle. In conclusion, Jigsaw technique can improve students? reading comprehension on descriptive text.Keywords: Improve, Students, Reading, Jigsaw, Descriptive Text.